Weaving in a Foreign Land: Transmission of Textile Skills through Enslaved Women and through Intermarriages in the Ancient Eastern Mediterranean and Pontus - Alina Iancu (Fasciculi Archaeologiae Historicae)
In the ancient Eastern Mediterranean and beyond, textile production was a very dynamic activity where patterns of transmission of spinning and weaving skills through women can be traced over long distances. Even if it is traditionally believed that in antiquity lives of women were not so dynamic, several literary sources give consistent proofs of the mobility of women. For example, the “Iliad” is among the most important texts in providing instances of forced or willing migration of women highly skilled in the craft of weaving, e.g. Sidonian women brought by Paris to Troy for their craftsmanship, who made the most beautiful cloth from Hecuba’s house (Hom. Il. 6.288-305), to Hector’s vision of his wife, Andromache, carried as slave to Argos and forced to spin for her future mistress (Hom. Il. 6.454-456). The view from the archaeological and iconographic evidence is consistent with that drawn from the literary record. Thus, we can follow the literary sources supported by iconography and archaeology to identify patterns of transmission of textile crafts through women in an effort to gain a better understanding of the dynamics of textile production in the ancient Greek world.